STRUCTURE AND POSSIBILITIES OF PM «SOLVING ENVIRONMENT» OF INTEGRATED PROGRAMMATIC ENVIRONMENT «MATHLOGIC V.2» - Scherbina, O.V.; Peschanenko, V.S.; Lvov, M.S. (Journal of Information Technologies in Education (ITE), 2009)
This article presents the PM ‘Solving environment’ of integrated programmatic environment Mathlogic v.2, (ML2) which was made within the framework of project of Terra Mathematica in the Laboratory of Pedagogical Software Development and Implementation. The article describes the structure of PM «Solving environment», exposes features of its functionality, and also technologies and methods which were used for their realization.